2016
DOI: 10.1038/srep30382
|View full text |Cite
|
Sign up to set email alerts
|

Generation and protective efficacy of a cold-adapted attenuated avian H9N2 influenza vaccine

Abstract: To prevent H9N2 avian influenza virus infection in chickens, a long-term vaccination program using inactivated vaccines has been implemented in China. However, the protective efficacy of inactivated vaccines against antigenic drift variants is limited, and H9N2 influenza virus continues to circulate in vaccinated chicken flocks in China. Therefore, developing a cross-reactive vaccine to control the impact of H9N2 influenza in the poultry industry remains a high priority. In the present study, we developed a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Contrasting the results from chickens, the riMLIV in ferrets was transmitted to direct contact animals. Further safety mechanisms, like the generation of cold-adapted mutants 41,42 and/or the introduction of species-specific siRNA targets 22,43 , could be used to improve the applicability of the prototype as a vaccine for mammalian species. Interestingly, vaccine virus genome was recorded in nasal washing fluid of one naive direct contact sentinel, and that particular animal also seroconverted at a later time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting the results from chickens, the riMLIV in ferrets was transmitted to direct contact animals. Further safety mechanisms, like the generation of cold-adapted mutants 41,42 and/or the introduction of species-specific siRNA targets 22,43 , could be used to improve the applicability of the prototype as a vaccine for mammalian species. Interestingly, vaccine virus genome was recorded in nasal washing fluid of one naive direct contact sentinel, and that particular animal also seroconverted at a later time point.…”
Section: Discussionmentioning
confidence: 99%
“…The current MLIVs are based on apathogenic influenza viruses, and attenuation is, e.g. achieved by using truncated NS1 proteins 21 or restricted replication capacities due to cold-adaptation 22 or the introduction of elastasespecific cleavage sites into the HA precursor protein 23 . Although cold-adapted MLIVs have been licensed for several years for use in humans, there are no MLIVs licensed for poultry yet, and only two types of vector-based live vaccines are on the market 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Influenza virus of the H9N2 subtype also continues to circulate in vaccinated chicken flocks in China because the protective efficacy of inactivated vaccines against antigenic drift variants is limited [9]. Since the effectiveness of inactivated vaccines strongly depends on the antigenic match of the HA in the vaccine and the HA of the field virus, the antigenic diversity of avian influenza viruses has been recognized as the main challenge for the eradication of HPAIVs [9][10][11][12].…”
Section: Inefficiency Of Inactivated Vaccines In the Prevention Of VImentioning
confidence: 99%
“…Live cold-adapted influenza vaccine candidates were developed by serial passages of H9N2 viruses in chicken embryos at low temperature. It was shown that the obtained mutant viruses protect chickens from homologous and heterologous strains of H9N2 subtype [9,40].…”
Section: Vaccines Based On Temperature-sensitive Mutantsmentioning
confidence: 99%
See 1 more Smart Citation